Computed Tomography (CT) Finding on Nasopharyngeal Carcinoma - Elvita Rahmi Daulay (INTERNATIONAL JOURNAL OF NASOPHARYNGEAL CARCINOMA, 2021)
Introduction: Nasopharyngeal carcinoma (NPC) is cancer come from nasopharynx epithelium. Nasopharyngeal carcinoma is a frequent cancer in Indonesia and in the fifth position for the most common tumor and first position for the most common malignancy in the head and neck. The signs and symptoms of nasopharyngeal carcinoma can be unspecific. Radiological examination of suspect NPC is an important diagnostic investigation. Staging of nasopharyngeal carcinoma is based on the analysis of the primary tumor, lymph node involvement, and the status of distant metastasis (M category). Case report:  We reported three patients with nasopharyngeal carcinoma in Adam Malik General Hospital that was diagnosed by histopathology biopsy and undergo Nasopharynx Computed tomography (CT) examination. The study aimed to present CT findings of the patients. Conclusion: Imaging modalities include contrast enhanced computed tomography (CT) has been used for staging and evaluation. The main objective of the radiological examination are provide a more definite diagnosis of suspected tumor in the nasopharynx., determine the more precise location of the tumor, determine the size of the tumor, and finding and determine the extent of the spread of the tumor to the surrounding tissue, where extensive invasion can be found as anteriorly, lаterаlly, posteriorly, inferiorly, and superiorly